Small Ruminant Community Breeding Program in Indonesia - Bess Tiesnamurti; S E Sinulingga; R M Gatenby (Indonesian Center for Animal Research and Development, 2020)
This paper outlines the principles of community breeding programs, reviews similar programs that have been conducted in Indonesia, as well as proposing improvements. Community breeding programs (CBP) are a method for genetic improvement of livestock, with voluntary participation of farmers, using animals belonging to the farmers, by defining breeding objectives and selection criteria or traits, selecting the best males of the group, performance testing and distributing males to the farmers. Farmers have the ownership of the program and contribute to the sustainability of the program, marketability of the products according the needs of the farmers, as well as strengthening farmers institutions. There are breeding scehemes of one tier, two tier and three tier that can be implemented to achieve the goals of genetic improvement. Several CBP has been carried out scatteredly, however improvements have to be made such as by long term financial support, strong commitment from breeders, mentoring by academias, data management and analysis as well as economic assessment. Therefore, a more masive and sustainable CBP should be conducted to improve the genetic quality of sheep and goat in Indonesia.